Investigating Ethnomathematics in Traditional Farming in Bitefa Village, North Central Timor District - Yohanis Ndapa Deda; Stanislaus Amsikan; Otaget Daniel; Maya Purwaningsi Lasfeto (RANGE: Jurnal Pendidikan Matematika, 2026)
The community of Bitefa Village in North Central Timor Regency (TTU) keeps farming corn on dry land as they have done for generations, but they are not aware of the mathematical activities that could be used as a source of mathematics education. The purpose of this study is to explore ethnomathematical activities in the dryland farming culture of corn cultivation in Bitefa Village.  The research method is qualitative with an ethnographic approach. Spradley's ethnographic approach research sequence is used to identify, classify, and interpret ethnomathematical activities embedded locally in traditional dry farming. Data collection is through participatory observation, interviews, and recording of agricultural artefacts. Analysis was conducted using Spradley's research sequence approach, domain analysis, taxonomic analysis, component analysis, and cross-domain theme analysis. The results show that spatial planting patterns aim to facilitate weeding and root competition; informal cultural units of measurement are used with functional adequacy and selective metric verification; seasonal decision-making based on local phenological indicators; a hierarchical aggregation system for crop yields (Pulir-Ikat-Kuda) that facilitates calculation, exchange, and estimation; and ritual-social mechanisms that legitimize and coordinate collective agricultural efforts. This study suggests that applying mathematical exercises to traditional corn farming methods, such as comparing or converting local units to standard units and forecasting corn seeds based on farm size, could be a source of learning in mathematics education in the classroom.